Challenges of free data flow between the EU and US: can EU-US privacy shield ensure co-operation? - Artjoms, Jurkevics (Riga Graduate School of Law, 2020)
The following thesis aims to provide an insight into the way US and EU data protection regulations compare to each other and how those can harmonized in the future with an idea to make it easier to understand how cross-country business might operate in this environment and whether there could be any harmonization opportunities to provide less burden on businesses in trying to comply with different laws across Atlantics. The research question of the thesis therefore is “Is current framework for data transfers between EU-US relevant and stable for future challenges in data protection field?” and “If not, then how two legal systems can be better harmonized based on the analysis of both of them?”
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Private law::Commercial and company law; Data protection